2008
DOI: 10.5007/2175-8026.2008n55p15
|View full text |Cite
|
Sign up to set email alerts
|

Production and identification of English word-final nasal consonants by Brazilian EFL learners

Abstract: Abstract Abstract AbstractThis preliminary study aims at investigating the production and perception of the English nasals /m/ and /n/ in word-final position by a group of 10 intermediate Brazilian EFL learners. Production data was collected by means of a Sentence Reading Test considering preceding vowel as phonological context. Perception was assessed by means of an identification test contrasting native-like vs. nonnative-like pronunciation of the target nasal consonants. The results from production suggest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Another pervasive phonological process is Vocalization of Nasals. Kluge and Baptista (2008) argue that [m] triggers higher Vocalization rates because the word-final m grapheme is highly frequent in BP words (e.g., com 'with'), while n only occurs in few words (e.g., hífen 'hyphen'). Thus, Brazilians tend to associate the m grapheme more often with the L1 phonological process and vocalize the wordfinal nasals in words spelled with m. The findings of the present study challenge this explanation, indicating that the silent -e condition inhibits the occurrence of Vocalization, and that the words that are not spelled with silent -e are vocalized more often when they are spelled with n. Clearly, this issue deserves further investigation, but the present study has confirmed the persistence of Vocalization of Nasals in the interphonology of learners from different proficiency levels and living in an L2 context.…”
Section: Rq1: Frequency Of Phonological Processes and L1 Sound-spellimentioning
confidence: 99%
“…Another pervasive phonological process is Vocalization of Nasals. Kluge and Baptista (2008) argue that [m] triggers higher Vocalization rates because the word-final m grapheme is highly frequent in BP words (e.g., com 'with'), while n only occurs in few words (e.g., hífen 'hyphen'). Thus, Brazilians tend to associate the m grapheme more often with the L1 phonological process and vocalize the wordfinal nasals in words spelled with m. The findings of the present study challenge this explanation, indicating that the silent -e condition inhibits the occurrence of Vocalization, and that the words that are not spelled with silent -e are vocalized more often when they are spelled with n. Clearly, this issue deserves further investigation, but the present study has confirmed the persistence of Vocalization of Nasals in the interphonology of learners from different proficiency levels and living in an L2 context.…”
Section: Rq1: Frequency Of Phonological Processes and L1 Sound-spellimentioning
confidence: 99%